The role of public libraries in promoting lifelong learning - Magdalera, Myla V.; Apolinario, Rhea Rowena U.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
This study examined the extent by which Philippine public libraries advance lifelong learning while also determining the expectations of the clients pertaining to such. It also aimed to develop programs for Philippine public libraries that advance lifelong learning based on the outcome of the data gathered for this study. The study was done in the city libraries in Metro Manila, using survey questionnaires, observation, and document analysis. The findings revealed the function of public libraries in promoting lifelong learning. It also revealed the inadequacy of activities and resources. It is hoped that the findings of the study will persuade the government of the Philippines to reconsider the role of public libraries in the lifelong learning of the citizens of the country. Recommendations and programs are made particularly toward improving public libraries in the Philippines.
Thesis
Keywords: Public libraries -- Philippines